Right diaphragmatic hernia with a late onset - Neicy María Hernández Fernández; José Muñiz Escarpanter; Manuel Alejandro Alvaredo Soria (Acta Médica del Centro, 2013)
Congenital diaphragmatic hernia is the communication between the thoracic and abdominal cavities due to a diaphragmatic defect that exists since the intrauterine stage. It usually occurs on the left side and appears in the neonatal stage as a respiratory distress in the newborn. Definitive treatment is always surgical. The case of a patient with a diaphragmatic hernia located on the right side is reported. It appeared after one year of age and it was diagnosed and operated with satisfactory results.